Unusual occurrence of two species and rare occurrence of one species of’ neritic squids off Mangalore coast - Mohamed, K S; Nagaraja, D (Indian Journal of Fisheries, 2011)
Unusual occurrence of two species and rare occurrence of one species of’ neritic squids off Mangalore coast